THE ROLE OF POLYMORPHISM OF LIPID METABOLISM GENES IN THE PATHOGENESIS OF PREECLAMPSIA - Артем Алексеевич Денисов; Анастасия Константиновна Петриченко; Надежда Васильевна Башмакова; Татьяна Борисовна Третьякова; Наталья Борисовна Давыденко; Людмила Анатольевна Пестряева (The Publishing House Medicine and Enlightenment, 2023)
Violation of lipid metabolism with the formation of atherogenic factors and subsequent endothelial dysfunction is one of the concepts explaining the pathogenesis of preeclampsia. Polymorphism of ApoE, CETP, and LPL genes can influence the course of pregnancy, provoking maternal dyslipidemia. The aim of the study - to study the clinical and anemnestic features of patients with preeclampsia and women with a high risk of preeclampsia; to compare the data of biochemical tests of the data of both groups of patients, as well as to determine the role of polymorphism of lipid metabolism genes as risk factors for preeclampsia. Materials and methods. A prospective cohort comparative study of 60 patients was conducted, of which the main group consisted of 30 women with moderate and severe preeclampsia and 30 patients with a high risk of developing preeclampsia according to prenatal screening of the first trimester, who made up the comparison group. In the course of the study, anamnestic factors, features of lipid metabolism and the results of genetic studies were analyzed. Conclusion. The conducted studies showed a significant difference in the features of the obstetric and gynecological anamnesis of both groups of patients, lipidogram indicators, as well as in the distribution of alleles and genotypes in the group of women with realized preeclampsia by polymorphic markers ApoE 388 T>C and CETP 1264 G>A. There was no difference in the distribution of alleles and genotypes of the LPL 447 C>G gene.